2016
DOI: 10.3389/fmars.2016.00147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative High-Throughput Sequencing Methodologies for the Monitoring of Marine Picoplanktonic Biodiversity Based on rRNA Gene Amplicons

Abstract: Sequencing of rRNA gene polymerase chain reaction amplicons (rRNA tags) is the most common approach for investigating microbial diversity. The recent development of high-throughput sequencing (HTS) technologies has enabled the exploration of microbial biodiversity at an unprecedented scale, greatly expanding our knowledge on the microbiomes of marine ecosystems. These approaches provide accurate, fast, and cost efficient observations of the marine communities, and thus, may be suitable tools in biodiversity mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 75 publications
0
20
1
Order By: Relevance
“…This means that even if the same number of OTUs was found for V4 and V9, the proportion of each OTU was different. The V9 Simpson index of OSD80 and 123 (0.87 and 0.91, respectively) fall in the range of Simpson index calculated in similar environments: for example in Baffin Bay (0.88, Hamilton et al ., ) and off the Mediterranean Sea coast (0.92, Ferrera et al ., ), but the V4 Simpson index was lower (0.68 and 0.81 respectively).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This means that even if the same number of OTUs was found for V4 and V9, the proportion of each OTU was different. The V9 Simpson index of OSD80 and 123 (0.87 and 0.91, respectively) fall in the range of Simpson index calculated in similar environments: for example in Baffin Bay (0.88, Hamilton et al ., ) and off the Mediterranean Sea coast (0.92, Ferrera et al ., ), but the V4 Simpson index was lower (0.68 and 0.81 respectively).…”
Section: Discussionmentioning
confidence: 84%
“…An analysis of 2200 full 18S sequences of protists (Caron et al ., ) showed that building OTUs at 95% identity provided a number of OTUs close to the expected number of species, but the authors remarked that a 98% identity threshold provides a better taxonomic resolution that allows to investigate interspecific diversity. In the present study, OTUs were built at 97% identity for both the V4 and the V9 regions of the 18S rRNA gene, in agreement with a number of recent studies that used these markers (e.g., Massana et al ., ; Ferrera et al ., ; Hu et al ., ). Clustering regions with different sizes (V4: 450 bp and V9: 150 bp) at the same identity level should produce more diverse OTUs for V4 than for V9, although regions where nucleotide changes are concentrated do not cover the whole amplicons and can be of different length in V4 and V9.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality seems to play a major role in shaping bacterioplankton biodiversity and community structure (Gilbert et al, 2012;Cram et al, 2015) which could overwhelm the effects of human-induced pressures. Thus, despite being extremely promising, the suitability of incorporating prokaryotic/eukaryotic biodiversity into MSFD descriptors needs to be further explored in order to discriminate between changes resulting from human activities and the natural variability of the marine environment (Ferrera et al, 2016).…”
Section: Use Of Metabarcoding To Study Marine Biodiversitymentioning
confidence: 99%
“…Studies demonstrate DNA metabarcoding to be a reliable method for biodiversity assessment with potential for inferring biotic indices for marine ecosystem quality assessment (Aylagas et al, 2014;Pawlowski et al, 2014;Cowart et al, 2015;Elbrecht and Leese, 2015;Visco et al, 2015;Ferrera et al, 2016). Comparable results between molecular and traditional approaches are reported in a number of studies (Hirai et al, 2015a;Lejzerowicz et al, 2015;Aylagas et al, 2016Aylagas et al, , 2017Valentini et al, 2016), suggesting that assessment programs that require manually intensive sorting and visual inspection will be among the first to formally integrate molecular techniques.…”
Section: Applications Of Dna Sequencing To Marine Assessment Programsmentioning
confidence: 99%